Clinical evaluation of ethanolic extract of curcumin (Curcuma longa) on wound healing in Black Bengal goats (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was aimed at clinical evaluation of surgical wound healing in goats treated with ethanolic extract of turmeric (Curcuma longa) rhizomes through topical route.Materials and methods: Eighteen surgical wounds were made in nine goats. The goats were divided into three groups; Group 1 (test group) was treated with ethanolic extract of turmeric, Group 2 (standard group) was treated with Povidone iodine, and the Group 3 was kept as untreated control. Follow up information was recorded from day 0 to day 21 postoperatively. Some morphological characters such as swelling area of wound, elevation of suture line from the skin surface, width of the suture area and contraction length per week were considered to determine the healing process. Bacteriological evaluation was done by conventional bacteriological techniques, and the tissue biopsies were stained by hematoxylin and eosin stains for histopathological studies.Results: Swelling of suturing area (11.51±0.36 mm) and elevation of suture line (2.65±0.41 mm) were lowest in wounds treated with ethanolic extract of turmeric. In histopathological studies, it was seen that tissue debris and hemorrhages disappeared and a thin line of keratin layer reappeared on the epidermal surface of the wound treated with ethanolic extract of turmeric.Conclusion: Ethanol treated turmeric enhances wound healing process in goats. This result could help the veterinarian and the researchers to consider herbal product especially ethanolic extract of turmeric for the treatment and better healing of surgical wounds with minimal complications.http://doi.org/10.5455/javar.2017.d209XML    PubReader